Marriage Cancellation Due to Coercion from Marriage and Islamic Law Perspectives - Vanisa Vinabilah; Hazar Kusmayanti; Fatmi Utarie Nasution (Alauddin Law Development Journal)
This study analyzes preventive and repressive legal protection for injured parties in marriages carried out on the basis of coercion in relation to marriage law and Islamic law. The methods used were the juridical normative. The results showed that preventive and repressive legal protection is very important in preventing and handling cases of marriages carried out based on coercion and threats. Preventive protection, such as counseling to the community, pre-marital guidance by the KUA, and the role of the family in increasing awareness of the right to freedom in choosing a life partner. Implementing repressive measures such as filing for marriage annulment and reporting criminal acts based on threats is essential to ensure justice for victims. There must be legal safeguards that guarantee that all marriages are based on the voluntary consent of the bride and groom, as expressly stated in the marriage and Islamic compilation law.